PENGARUH GOOD CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP KINERJA KEUANGAN PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN - Dwi Utami; Chasan Azari; Yanda Bara Kusuma (Faculty of Social and Political Science, 2020)
A good corporate governance and financial leverage are necessary for a company. This study aims to determine the influence of good corporate governance and leverage towards the financial performance of food and beverage companies listed on the IDX (Indonesia Stock Exchange) in period (2013-2017). The supporting variable includes good corporate governance determined by the board of commissioner, the independent commissioner, the audit committee, and the managerial ownership, leverage through the DAR (Debt-Asset Ratio), and financial performances determined by ROA (Return on Assets). The study analyzes four companies based on purposive sampling. The technique of analysis uses multiple linear regression with the IBM SPSS statistic version 24. The result indicates that good corporate governance which determined by the board of director; the independent commissioner, the audit committee, the managerial ownership, and the leverage variable simultaneously have a significant effect on the company performance. Partially, the capacity of the board of commissioner, the independent commissioner, the audit committee, and the managerial do not have a significant influence in the company performance. Both of the independent commissioner and the leverage have a negative influence. However, independent commissioner significantly influenced the company financial performances, while the leverage doesn’t significantly influence it.